Smoking Cessation in Long-Term Conditions: Is There "An Opportunity in Every Difficulty"?. (8th December 2013) - Siddiqi, Kamran; Dogar, Omara F.; Siddiqi, Najma
Abstract : Introduction . Smoking plays a causal role in several long-term conditions and worsens their outcomes. Focusing on six such conditions, we present a narrative review of seminal studies on the prevalence and impact of continued tobacco use on these conditions; the effectiveness of cessation interventions; the extent to which patients receive these interventions, and barriers to providing and taking up these interventions. Methods . A conceptual framework was used to identify questions for a series of focused literature reviews. Findings were synthesized and the literature was examined to identify themes common across these conditions. Results . Smoking prevalence is either similar or higher in patients with established long-term conditions compared to the general population. Continued smoking accelerates disease progression, worsens outcomes, and risks poor treatment compliance or further complications. There is strong evidence for the effectiveness of cessation interventions in achieving smoking abstinence. Despite this, only a small proportion of patients receive such interventions. Important barriers to uptake include concerns about weight management and drug safety, higher nicotine dependency and codependency, comorbidity, and misperceptions about the benefits of cessation. Conclusion . The benefits of offering smoking cessation in patients with long-term conditions are far too great for it to remain of a low priority.